2021
DOI: 10.1111/trf.16313
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DRB1 molecules and the presentation of anchor peptides from RhD, RhCE, and KEL proteins

Abstract: Background Antigens from the Rh and Kell systems are recognized as the most immunogenic in clinical practice. This study evaluated the possible molecular mechanisms involved in the interaction of antigenic peptides with the DRB1 molecules, which help to explain the high frequency of anti‐K and association of D + C antibodies in transfusion and incompatible pregnancy. Study Design and Methods We included 201 patients with antibodies against antigens from the Rh and Kell systems and compare them with 174,015 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…HLA‐DRB1*07 was undetected in patients with anti‐K antibody, which was the third most common antibody in the study. This is comparable to the results of De Souza et al, who demonstrated a very low frequency of HLA‐DRB1*07 in individuals with anti‐K [20]. The association of this HLA allele with RBC Ab development has been demonstrated in patients who develop RBC Abs with neither a history of receiving blood components nor previous pregnancies.…”
Section: Discussionsupporting
confidence: 88%
“…HLA‐DRB1*07 was undetected in patients with anti‐K antibody, which was the third most common antibody in the study. This is comparable to the results of De Souza et al, who demonstrated a very low frequency of HLA‐DRB1*07 in individuals with anti‐K [20]. The association of this HLA allele with RBC Ab development has been demonstrated in patients who develop RBC Abs with neither a history of receiving blood components nor previous pregnancies.…”
Section: Discussionsupporting
confidence: 88%